The Relationship Between Family Support And Dietary Adherence Among Hypertension Patients - Alfi Laily Ayu Rohmawati; Sulton Wariin (Journal of Nursing Periodic, 2026)
Introduction: The high incidence of hypertension has positioned this non-communicable disease as a major challenge in the public health sector. Successful blood pressure control depends strongly on patients' discipline in maintaining their diet. Field phenomena indicate that compliance with nutritional regulation is still frequently neglected by patients. In this context, the active involvement of the closest people becomes a crucial element in encouraging patients' dietary discipline. This study aim to determine the relationship between family support and dietary adherence among patients with hypertension Methods: The methodology used was quantitative correlational research with a cross-sectional design. A total of 63 participants were included as samples through quota sampling. Data were collected using questionnaire instruments that measured family support and dietary adherence variables, which were subsequently tested statistically using Spearman Rank. Results: The empirical findings indicated that most respondents received social assistance from their families at moderate to optimal levels, in line with dietary adherence that was mostly in the adherent category. Statistical analysis produced a value of p = 0.002 (α = 0.05), indicating a significant relationship with a moderate level of association between the two variables. Conclusions: Family support is significantly associated with dietary adherence among patients with hypertension. Better family support is related to higher patient adherence to the recommended hypertension diet. Therefore, family involvement should be strengthened as part of sustainable hypertension management.